Rituximab in the treatment of interstitial lung disease associated with antisynthetase syndrome: a multi-center retrospective case review - Doyle, Tracy J. (J Rheumatol, 2018)
OBJECTIVE: To assess clinical outcomes including imaging findings on computed tomography (CT), pulmonary function testing (PFT), and glucocorticoid use in patients with the antisynthetase syndrome (AS) and interstitial lung disease (ILD) treated with rituximab (RTX). METHODS: We retrospectively identified all patients at two institutions with AS-ILD who were treated with RTX. Baseline demographics, PFTs and chest CTs were assessed before and after RTX. Two radiologists independently evaluated CTs using a standardized scoring system. RESULTS: Twenty-five subjects at the Brigham and Women’s Hospital (n=13) and University of Pittsburgh Medical Center (n=12) were included. Antisynthetase antibodies were identified in all patients (16 Jo-1, 6 PL-12, 3 PL-7). In 21 cases (84%), the principal indication for RTX use was recurrent or progressive ILD due to failure of other agents. Comparing pre- and post-RTX pulmonary parameters at 12 months, CT score and FVC% were stable or improved in 88% and 79% of subjects, respectively. TLC% increased from 56±13 to 64±13 and glucocorticoid dose decreased from 18±9 to 12±12mg/day. Although DLCO% declined slightly at 1 year, it increased from 42±17 to 70±20 at 3 years. The most common imaging patterns on CT were NSIP (n=13) and UIP/fibrotic NSIP (n=5), of which 5 had concurrent elements of COP. CONCLUSIONS: Stability or improvement in pulmonary function or severity of ILD on CT was seen in most patients. Use of RTX was well tolerated in the majority of patients. RTX may play a therapeutic role in patients with AS-ILD and further clinical investigation is warranted.